Mental Illness dan Self Care Behavior Perpetrator Non-Suicidal Self Injury Female Victims of Sexual Violence: A Phenomenological Study - Raden Deceu Berlian Purnama; Suhertina; Ku Hidayatullah Binti Ku Ismail; Regita Cahyani Putri; Hasgimianti; Raja Rahima Munawarah Raja Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The objectives of this study are: 1) gaining knowledge about the forms of mental illness experienced by perpetrators and 2) gaining knowledge about the self-care behavior abilities of perpetrators of NSSI who are victims of sexual violence. This study uses a phenomenological approach, Located in Pekanbaru. The number of research informants is 5 victims of sexual violence who commit NSSI through a purposive sampling technique. Data collection using open-ended interview techniques and observation. This research uses Husserl's phenomenological approach, the data is analyzed using the Colaizi 1978 model, namely the data is read repeatedly, extracting significant statements, coding meaningful and important statements, inserting them into themes, describing in detail and unambiguously, identifying common points of view and sublimation of thematic concepts, validating the participants. The results of this study indicate the types of mental illness experienced by NSSI perpetrators are 1) anxiety disorders, of the realistic type with avoidant and attached behavioral patterns and social anxiety disorders, 2) post-traumatic stress experienced by informants of the complex, chronic PTSD type, and comorbidities strengthened by the following factors: committed by a close person, accompanied by physical torture, the victim hides the fact of violence and lack of social support from the family. Self-care of female, namely: 1) self-physical care; the informant is reluctant to take care of themselves physically; 2) psychological care; the informant is serious about recovering psychologically; 3) spiritual care; the research informant tries to stay connected with God; and 4) the informant's professional life continues with various motives.